2005
DOI: 10.1159/000085666
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic insights into the ageing syndrome Hutchinson-Gilford Progeria (HGPS)

Abstract: Hutchinson-Gilford Progeria Syndrome (HGPS) is an extremely rare genetic disorder characterized by premature ageing in childhood and serves as a valuable model for the human ageing process in general. Most recently, point mutations in the lamin A (LMNA) gene on chromosome 1q have been associated with the disease, however how these mutations relate to the complex phenotype of HGPS remains to be established. It has been shown that fibroblasts from HGPS patients are frequently resistant to immortalization with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Suppression of proliferation defects associated with progerin expression has not been reported previously, although investigators have found that hTERT expression will immortalize HGPS fibroblasts (Wallis et al, 2004;Corso et al, 2005;Huang et al, 2005). Because the suppressive effects of hTERT are apparent immediately after hTERT expression, we disfavor a model whereby enhanced telomere length is a primary determinant.…”
Section: Discussionmentioning
confidence: 81%
“…Suppression of proliferation defects associated with progerin expression has not been reported previously, although investigators have found that hTERT expression will immortalize HGPS fibroblasts (Wallis et al, 2004;Corso et al, 2005;Huang et al, 2005). Because the suppressive effects of hTERT are apparent immediately after hTERT expression, we disfavor a model whereby enhanced telomere length is a primary determinant.…”
Section: Discussionmentioning
confidence: 81%
“…Some reports indicate that hTERT-mediated cellular immortalization is possible in certain HGPS strains (34,44,45), while others have found that HGPS fibroblasts are resistant to hTERT immortalization (46,47). Moreover, hTERT does not protect against progerin-induced aberrant nuclear shape and DNA damage (48).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical weakening of vascular endothelial and smooth muscle cells could be the initiating pathological event that leads to arteriosclerosis (Davies, 1995;Mounkes & Stewart, 2004) or at least add to other cellular defects seen in HGPS such as genetic instability and premature cellular senescence (Mounkes & Stewart, 2004;Corso et al, 2005;Liu et al, 2005;Varela et al, 2005;Kudlow et al, 2007). Since vascular smooth muscle cells (VSCM) and endothelial cells were shown to be the primary targets of progerin build-up (McClintock et al, 2006) and are constantly exposed to fluid shear stress and strain in the vessel wall, increased cellular sensitivity to mechanical stress and impaired cell cycle activation may predominantly affect vascular cells and, therefore, contribute to arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%